France : Financial Sector Assessment Program-Technical Note on Stress Testing the Banking Sector. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2013)
This technical note discusses key findings of the Stress Testing of the Banking Sector for France. Stress testing analysis was used to capture the most salient risks for banks. The findings support the current focus of Autorite de Controle Prudentiel (ACP) to require banks to build up adequate capital and liquidity buffers. They suggest that the banking system would be able to meet regulatory ratios under most scenarios. Solvency stress tests indicate that banks could cope with deterioration in the economic environment while phasing in capital requirements under Capital Requirements Directive IV.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet